Acho que nunca antes na história deste país... modalização epistêmica deôntica e modalização epistêmica em cartas de leitores do período eleitoral para presidência da república - Gonçalves, Tatiana Jardim (2012)
In this dissertation, we analyze and interpret the expression of deontic modality and epistemic modality in readers' letters and the different argumentative orientations that make this textual genre possible. We verify also interfaces with the study of the referenciation and polyphony, because modalizing is also build and (re) construct objects of discourse, and also make it possible to insert through other voices, other points of view in the statement . To develop the study, we adopted a conception of language as practice, discourse postulated by Benveniste (2005). Regarding the aspect of argument, adopted the theory of argumentation in language formulated by Ducrot (1976,1987,1989). In the approach to the referenciation were considered Mondada and Dubois (2003) and Neves (2006) postulates . To address the semantic-pragmatic aspects of modality, appealed to Pinto (1994) and Koch (2009). The question of genre has been treated from the sociorhetoric perspective postulated by Bazerman (2006). The corpus consists of thirty (30) letters from readers, fifteen (15) of O Globo newspaper in print and 15 (fifteen) of the Jornal do Brazil in digital version. The letters were collected between August 1 and October 3, 2010, considering the issue elections for the presidency in Brazil. For the analysis, we observed the effects of deontic modality and epistemic modality, lexical items backers of resources and the effects of meaning arising from language use that mark. It was possible to verify that the use of the deontic or epistemic modality depends of the enunciation, it means, the occurrence of these linguistic marks results from the intersubjective cooperative process of language use